Exploring the Therapeutic Promise of Free Fatty Acid Receptor 4 in Diabetes Mellitus: A Deep Dive into Molecular Mechanisms and Future Perspectives - Jithin Mathew, (Asian Journal of Pharmaceutics (AJP), 2024)
Free fatty acid receptor 4 (FFA4) is encouraged by extended-chain fatty acids and has gained recognition as a promising agent for the treatment of diabetes mellitus (DM) treatment. Research indicates that FFA4 functions as a receptor for detecting unsaturated long-chain fatty acids, shedding light on the cellular pathways through which these fatty acids influence various biological functions. These mechanisms include the secretion of digestive tract peptide hormones and the control of glucose level. Activation of FFA4 is linked to enhanced insulin susceptibility and decreased release of glucagon-like peptide 1 from enteroendocrine cell types, making it an appealing target for developing therapies for overweight and diabetes. Agonists of FFA4 have demonstrated potential in enhancing satiety, stimulating incretin release, mitigating inflammatory metabolic responses, and boosting insulin sensitivity. As a result, drugs targeting FFA4 are anticipated to become available soon. This review explores FFA4’s role in managing key metabolic processes, such as adipogenesis, lipid metabolism, and glucose regulation. It also assesses the potential of FFA4-based therapies for treating DM, emphasizing the progress and future directions in this evolving field of metabolic research.